1998
DOI: 10.1128/aem.64.2.543-548.1998
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycoplasma hyopneumoniae by Air Sampling with a Nested PCR Assay

Abstract: This article describes the first successful detection of airborneMycoplasma hyopneumoniae under experimental and field conditions with a new nested PCR assay. Air was sampled with polyethersulfone membranes (pore size, 0.2 μm) mounted in filter holders. Filters were processed by dissolution and direct extraction of DNA for PCR analysis. For the PCR, two nested pairs of oligonucleotide primers were designed by using an M. hyopneumoniae-specific DNA sequence of a repeated gene segment. A nested PCR assay was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(53 citation statements)
references
References 19 publications
3
48
0
2
Order By: Relevance
“…The process of nesting almost always decreases the detection level. Stark et al (1998) observed a 10 4 increase in sensitivity by using nested primers, although the increase is usually approximately 1-2 orders of magnitude.…”
Section: Effective Pcr Detection Levels and Inhibitionmentioning
confidence: 98%
See 3 more Smart Citations
“…The process of nesting almost always decreases the detection level. Stark et al (1998) observed a 10 4 increase in sensitivity by using nested primers, although the increase is usually approximately 1-2 orders of magnitude.…”
Section: Effective Pcr Detection Levels and Inhibitionmentioning
confidence: 98%
“…Samples on solid supports were eluted with 0.1% Triton X-100 solution and ground in liquid nitrogen to lyse spores. DNA was purified by phenol:chloroform extraction and DNA concentrated and cleaned by a spin column Aerosols sampled from pig rooms on seven commercial farms, Mycoplasma hyponeumoniae, nested PCR increased sensitivity by 10 4 times (Stark et al, 1998) 0.2 mm polyethersulfone filters at 8.3-20 L min À1 Filters were dissolved in chloroform, shaken, and then DNA was extracted from the solution by phenol:chloroform extraction, followed by ethanol precipitation and centrifugation of DNA Outdoor wastewater treatment plant, chemical plant, and indoor office building, Legionella spp., PCR more sensitive than plate counts (Pascual et al, 2001) Impacted onto a petri dish containing 20 mL of phosphate buffered saline, flow at 100 L min À1 Cells concentrated by centrifugation and lysed by freeze-thaw process. No purification Indoor and outdoor urban aerosols, Pneumocystis carinii, limit of detection was 10 2 cells without inhibition (Maher et al, 2001) 0.45 mm polyvinylidene difluoride filters at 0.4 L min À1 for 24 h Cells were lysed directly on the filter using extraction buffer and DNA was purified by phenol:chloroform followed by ethanol precipitation.…”
Section: -96 Hmentioning
confidence: 99%
See 2 more Smart Citations
“…Airborne spread of swine pathogens has been a topic of discussion in the last decades. There are reports on the detection of swine pathogens (bacteria and virus) in air samples (Bourgueil et al, 1992;Torremorell et al, 1997;Stark et al, 1998;Hermann et al, 2008;Weesendorp et al, 2008;Dee et al, 2009;Verreault et al, 2010). In addition, studies conducted in pigs to understand the regional spread of porcine reproductive and respiratory syndrome virus (PRRSv) and Mycoplasma hyopneumoniae confirmed that viable pathogens could travel between 3.5 and 9.1 km from the presumed source of infection Otake et al, 2010).…”
Section: Introductionmentioning
confidence: 99%